Inventarisasi Dan Identifikasi Penyakit Pada Tanaman Cabai (Capsicum annum L.) Di Desa Ujong Tanjong Kabupaten Aceh Barat - Agustinur Agustinur; Marwiah Marwiah; Chairudin Chairudin; Vina Maulidia; Siti Aminah (Jurnal Agrotek Lestari, 2026)
Red chili (Capsicum annuum L.) is a strategic commodity whose productivity is often hindered by pathogen attacks. This study aims to inventory the types of diseases and characterize the pathogens based on morphology and damage symptoms in Ujong Tanjong Village, West Aceh Regency. The research was conducted using a survey method with a purposive sampling technique for field observations, followed by laboratory characterization including pathogen isolation on Potato Dextrose Agar (PDA) and confirmation via Koch’s Postulates. The results identified four major diseases: Fusarium wilt, leaf spot (Cercospora sp.), fruit rot (anthracnose), and chili leaf curl virus (CLCV). Fusarium wilt was found to be the most dominant threat, with the highest disease incidence of 34.13% and a severity index of 12.23%. Morphological characterization of the isolates showed distinct features consistent with field symptoms, including the presence of pink conidial masses in the anthracnose isolates. Koch’s Postulates validated all isolates as the causal agents with high virulence, where clinical symptoms emerged within 14–21 days post-inoculation. In conclusion, soil-borne pathogens are the primary biotic constraint in the coastal areas of West Aceh, exacerbated by microclimatic conditions with high humidity. The implications of this study highlight the urgency of implementing integrated disease management, particularly the use of biological control agents and farmer education on field sanitation techniques, to prevent further yield loss and maintain regional chili production stability.Keywords: West Aceh, Red Chili, Disease Inventory, Fusarium Wilt, Koch’s Postulates.